Friction stir channeling in AA6082 and AA2024 dissimilar alloys - Vishwakarma P.; Upadhyay V.; Sharma C.; Yusufzai M.Z.K. (My University, 2025)
This work presents the effect of rotary speed (RS) and traverse speed (TS) on channel characteristics and weld tensile strength during simultaneous channeling and friction stir welding of dissimilar aluminium alloys 6082 and 2024. TS had discernible effect on the location of channels and shifted the same from advancing side to retreating side of weld joint. The effect of TS on channel area was found reverse to that of RS up to mid value of investigated range and beyond that they followed the same trend. RS had more dominating effect on the channel area than TS. The effect of TS and RS on channel perimeter was identical to that on channel area. It is possible to control the shape and size of channels and also their location by selecting proper combination of processing parameters during simultaneous friction stir channelling and welding of dissimilar aluminium alloys. © 2019 Elsevier Ltd.